2015
DOI: 10.3928/01913913-20141230-07
|View full text |Cite
|
Sign up to set email alerts
|

Confluent Diode Laser Coagulation: The Gold Standard of Therapy for Retinopathy of Prematurity

Abstract: The DLC method was significantly more effective than single-spot DLC in the treatment of retinopathy of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…[14][15][16][21][22][23] ). When comparing the methods of single spots and near confluent photocoagulation, the method of dense laser photocoagulation seems to be more effective and safer [23][24][25] . The complications of the CALCR procedure do not vary in principle from the complications that are described in standard methods of treatment with laser and cryocoagulation under the visual control of an indirect ophthalmoscope [12][13][14][15][16]19,20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][21][22][23] ). When comparing the methods of single spots and near confluent photocoagulation, the method of dense laser photocoagulation seems to be more effective and safer [23][24][25] . The complications of the CALCR procedure do not vary in principle from the complications that are described in standard methods of treatment with laser and cryocoagulation under the visual control of an indirect ophthalmoscope [12][13][14][15][16]19,20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Nine 10,25-32 included documents were obtained through systematic search, one 33 came from bibliographies of published papers, ten [34][35][36][37][38][39][40][41][42][43] were found using Google and three [44][45][46] were obtained from one of the authors. Publication dates ranged from 2005 to 2020.…”
Section: Overview Of Publicationsmentioning
confidence: 99%
“…In four countries the authors based their recommendations on previously published ROP guidelines 36,41,43,46 (1 LMIC, 1 UMIC, 2 HICs). A systematic review was carried out during the development of four guidelines 10,25,32,36 (1 LMIC, 2 UMICs, 1 HIC), and was possibly used in developing the Philippine (PAO) guidelines (LMIC).…”
Section: Quality Of the Evidencementioning
confidence: 99%
“…Laser photocoagulation is the standard of treatment choice in an attempt to slow down or reverse the growth of abnormal blood vessels and scar tissue formation despite problems such as visual field loss and development of myopia. 4 , 5 Recent research studies have shown that although laser treatment produces excellent results, 10% of the patients still may have unfavorable results. 6 …”
Section: Introductionmentioning
confidence: 99%